Ex vivo evaluation of polyethylene cable compared to stainless steel cerclage wire in a canine fracture model - Day, Seila; Elder, Steven; Brookshire, Cooper; Jaffe, Michael H. (Frontiers in Veterinary Science, 2025)
IntroductionThe objective of this study was to compare the biomechanical stability of an ultra-high molecular weight polyethylene (UHMWPE) orthopedic cable system to stainless steel cerclage wire (SSW) fixation in cyclic four-point bending in a cadaveric fracture model.Materials and methodsA long oblique osteotomy model was employed using paired canine cadaveric femurs. The osteotomies were stabilized with either three UHMWPE cables (n = 10) or three 18 gauge stainless steel loop cerclage wires (n = 10). Cyclic testing was performed by applying increasing force at 2 Hz until construct failure, defined as ≥2 mm of actuator displacement. Data analyzed included cycles to failure, load at failure, and dynamic stiffness.ResultsThere was no statistically significant difference in any of the outcomes tested between constructs. Visible loosening was noted in all loop cerclage constructs. No visible loosening of the UHMWPE cable was noted.DiscussionThe results suggest that the UHMWPE cable’s resistance to failure was comparable to SSW in four-point bending. Additional biomechanical testing would be needed to assess for statistical significance as well as performance in torsion and compression or with adjunctive fixation methods. Future clinical studies in veterinary applications are needed to assess how the UHMWPE cable performs in vivo.